Applied architecture patterns on the Microsoft platform : an in-depth, scenario-driven approach to architecting systems using Microsoft technologies - Seroter, Richard; Ashkenazi, Ofer (Packt Pub., 2010)
An in-depth scenario-driven approach to architecting systems using Microsoft technologies with this book and eBook.